2005
DOI: 10.1038/sj.bjp.0706417
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in the streptozotocin‐induced diabetic apoE‐deficient mouse

Abstract: 1 Endothelial dysfunction plays a role in the development of atherosclerosis and diabetes-associated vascular disease and, in the streptozotocin (STZ)-induced apoE-deficient diabetic mouse, we report that, when compared to the citrate (CIT)-treated nondiabetic apoE-deficient control, acetylcholine (Ach)-mediated endothelium-dependent relaxation was reduced in the small mesenteric arteries (SMA) and the plaque-prone regions of the aorta from the STZ-diabetic mouse. 2 In the SMA the component of Ach-mediated rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 67 publications
(82 reference statements)
9
76
0
Order By: Relevance
“…This suggests baseline endothelial SK3 levels are not rate limiting for EDHinduced vasodilation in normal physiological conditions but could become so when the EDH pathway needs to be activated, e.g., during early diabetes. SK3 downregulation was previously observed in STZ-induced diabetic ApoE-deficient mice (22) or in the cavernous tissues of diabetic rats (32) but not in C57Bl/6 diabetic mice (27). In line with the latter results, SK3 was not downregulated by diabetes in our study.…”
Section: Lack Of Hyal1 Prevents Endothelial Dysfunctionsupporting
confidence: 81%
See 1 more Smart Citation
“…This suggests baseline endothelial SK3 levels are not rate limiting for EDHinduced vasodilation in normal physiological conditions but could become so when the EDH pathway needs to be activated, e.g., during early diabetes. SK3 downregulation was previously observed in STZ-induced diabetic ApoE-deficient mice (22) or in the cavernous tissues of diabetic rats (32) but not in C57Bl/6 diabetic mice (27). In line with the latter results, SK3 was not downregulated by diabetes in our study.…”
Section: Lack Of Hyal1 Prevents Endothelial Dysfunctionsupporting
confidence: 81%
“…The mRNA expression level of several components of the EDH pathway (22) in mesenteric arteries was screened using real-time RT-PCR. No difference among experimental groups was detected for connexins 37, 40, 43, and 45; SK channels SK1 and SK2; intermediate conductance potassium channel IK1; transient receptor potential (TRP) channels TRPV4 and TRPC1; and caveolin-1 (data not shown).…”
Section: Exploration Of the Edh Pathway Componentsmentioning
confidence: 99%
“…Gap junction pathways in retinal arteries [45] and gap junction activity in mesenteric arteries [24] from STZ-induced diabetic rats have been shown to be reduced, and Ding et al [46] demonstrated that Cx37 mRNA expression was reduced in small mesenteric arteries from STZ-induced diabetic apoEdeficient mice compared with nondiabetic apoE-deficient control mice. Furthermore, we have shown a decrease in gap junction activity in isolated renal arteries from the female 25-week-old OZRs, associated with decreases in connexin 40 protein levels and Cx40 mRNA expression (E. J Young and J. J Reid, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has to be emphasized that changes in Cx expression and function may not be the sole contributors to endothelial dysfunction, and multiple mechanisms contribute to the inhibited coronary vasodilatation in diabetic mice. In addition to the impaired GJIC by decreased Cx40 expression, we believe that the inhibited endothelium-dependent hyperpolarization in diabetic CA may also involve other mechanisms: for example, 1) dysfunctional coupling of Cx peptides and their spatial co-association with K ϩ channels (12,42), and 2) changes in expression and activity K ϩ channels in the vascular smooth muscle cells (13,26).…”
Section: Discussionmentioning
confidence: 99%